Probabilistic data collection protocols for energy harvesting wireless sensor networks. (14th November 2012) - Yoshida, Masaya; Kitani, Tomoya; Bandai, Masaki; Watanabe, Takashi; Chou, Pai H.; Seah, Winston K.G.
Energy harvesting from ambient energy sources including solar and vibration has been studied as a candidate for powering next generation wireless sensor networks. However, energy harvesting is unstable to supply a sensor node with energy, and a node cannot know whether its neighbouring nodes have enough energy to receive a data packet. In this paper, we propose two data collection protocols for energy harvesting wireless sensor networks called the Probabilistic ReTransmission protocol (PRT) and PRT with Collision Consideration (PRT–CC). The idea is to derive the appropriate number of times to retransmit a packet based on the reception probability and the active intervals computed by the receivers themselves while, in PRT–CC, each node computes the reception probability with packet collision consideration. The performance evaluation shows that the proposed protocols are able to achieve higher delivery ratio than the previous work, namely, Geographic Routing with Duplicate Detection (GR–DD) and GR–DD with Retransmission.